Consistency Analysis of Practice Orientation of the Healthy Enterprise Program in China - Min Yang; Liping Huang; Chunling Peng; Yonglin Luo; Fangfei Li; Xinyang Yu (BMC Public Health)
Abstract Background The establishment of Healthy Enterprises is a critical element of occupational health protection and a key initiative within the Healthy China Action. This study aimed to analyze the action patterns of enterprises across various industries in implementing best practices for Healthy Enterprises and to assess the consistency of their positive orientation. Methods Text analysis was used to examine the summary materials of 300 outstanding Healthy Enterprise cases selected by government authorities. Following the pre-processing of the text specifications using a text segmentation tool, the positive-oriented consistency of Healthy Enterprise practices across varying risk profiles was comprehensively explored through the examination of word frequency, a co-word matrix, and topic model analyses. Enterprises were categorized into high and low-risk groups based on the classification and management of occupational injury risks. Results Enterprises across various industries leveraged "management" as a pivotal instrument in fostering and developing healthy enterprises within their organizational framework. High-risk sector entities prioritized the prevention and control of occupational diseases and hazards in the production process, bolstering supervision over workplaces, facilities, employees, and training. Conversely, low-risk sector entities placed a premium on cultivating a health-centric cultural ambiance and service provisions, thereby exhibiting an obvious advantage in promoting organizational structures and augmenting employee health literacy. The co-word matrix analysis revealed that the key point of "management" in high-risk industries centered on hazards and facilities in production. Meanwhile, "management" in low-risk industries focused on services, hygiene, environment, training, activities, etc. The keywords within the Specification guideline were categorized into 3 themes: healthy workplace management, employee health services, specialized care for distinct demographics and a health-conscious culture. Enterprises in both risk groups encapsulated all pivotal facets related to the theme in terms of practices, effectiveness and inspiration, reflecting good consistency in action practices. Conclusion The commendable implementation of the Healthy Enterprise Program demonstrates a positive orientation and consistency in executing health promotion initiatives based on the standardized guidelines, which is crucial for fostering a health-supportive environment and effectively protecting the well-being of the workforce.